Sacubitril/valsartan in chronic kidney disease, the nephrologist point of view - Borja Quiroga; Antonio de Santos; David Sapiencia; Yamila Saharaui; Vicente Álvarez-chiva (Nefrología (English Edition), 2019)
Introduction: Sacubitril/valsartan reduces cardiovascular morbidity and mortality in patients with systolic dysfunction (SD). The aim of the present study was to assess the evolution of chronic kidney disease (CKD) patients after initiating sacubitril/valsartan. Methods: We included 66 consecutive CKD patients with SD followed up in outpatient care. Patients had to meet the inclusion criteria of having a New York Heart Association class II to IV, receiving maximum tolerated doses of optimal medical therapy and CKD stages 1–4. At baseline, comorbidities and epidemiological data were collected and low doses of sacubitril/valsartan were initiated. At month 1 and 3, doses of sacubitril/valsartan were increased up to the maximum doses if tolerated. In each visit, renal function and cardiac biomarkers were recorded. All the data were analyzed at the end of follow up (6 months). Results: Of the 66 patients, 42 (63 %) were men, with a mean age of 73 ± 15 years. Mean creatinine at baseline was 1.42 ± 0.5 mg/dl (glomerular filtration rate (GFR) estimated by CKD-EPI was 50 ± 19 ml/min/1.73 m2) and mean left ventricular ejection fraction (LVEF) was 31 ± 9 %. At the end of follow up, LVEF improved from 31 ± 9%–39 ± 15 % (p < 0.001). After one month of treatment, renal function improved up to 53 ± 21 ml/min/1.73 m2, p = 0.005. For the remaining follow-up time, GFR remained stable (mean at end of follow-up 51 ± 18 ml/min/1.73 m2). Seven patients (10.6 %) withdrew from treatment. Conclusion: In our experience, sacubitril/Valsartan is safe in CKD, offering stability in CKD progression after 6 months. Resumen: Antecedentes y objetivo: Sacubitrilo/valsartan ha demostrado ser eficaz en la reducción de la morbi-mortalidad cardiovascular en los pacientes con disfunción sistólica (DS). El objetivo del presente estudio fue analizar la evolución de pacientes con enfermedad renal crónica (ERC) tras el inicio de sacubitril/valsartán. Material y métodos: Se incluyó a 66 pacientes consecutivos que acudieron a las consultas externas de Nefrología, con ERC y DS. Los criterios de inclusión fueron: presentar una clase funcional II a IV de la New York Heart Association (NYHA) con el tratamiento médico optimizado y ERC estadios 1 a 4. Se recogieron datos basales epidemiológicos y de comorbilidad en el momento de inicio del fármaco. En los meses 1 y 3 se tituló la dosis de sacubitril/valsartán (en función de la tolerancia). En cada visita se recogieron datos analíticos de función renal y biomarcadores cardiacos, entre otros. Se analizaron los datos a los 6 meses (fin del seguimiento). Resultados: De los 66 pacientes, 42 eran varones (63%) con una edad media 73 ± 15 años. La creatinina media fue de 1,42 ± 0,5 mg/dL (filtrado glomerular CKD-EPI 50 ± 19 ml/min/1,73 m2) con una fracción de eyección del ventrículo izquierdo (FEVI) media de 31 ± 9. Al final del seguimiento, la FEVI mejoró significativamente (basal 31 ± 9 vs final 39 ± 15, p < 0,001). En cuanto a la función renal, el filtrado glomerular por CKD-EPI presentó mejoría al mes (50 ± 19 vs 53 ± 21 ml/min/1,73 m2, p = 0,005) que se mantuvo estable (filtrado glomerular al final del seguimiento 51 ± 18 ml/min/1,73 m2). Abandonaron el tratamiento 7 pacientes (10.6%). Conclusión: En nuestra experiencia, sacubitril/valsartán es seguro en los pacientes con insuficiencia renal crónica y estabiliza la función renal a los 6 meses. Keywords: Chronic kidney disease, Heart failure, Renal failure, Sacubitril/valsartan, Palabras clave: Enfermedad renal crónica, Insuficiencia cardiaca, Insuficiencia renal, Sacubitrilo/Valsartán